Sediment Fractions and Organic Materials in the Dumai River Estuary Waters, Riau, Indonesia - Cahyani Fitrah Tanjung; Irwan Effendi; Elizal elizal (Asian Journal of Aquatic Sciences, 2018)
The purpose of this researched was to analize the consistency of organic material and sediment fraction on estuary in dumai river. The research was with purposive sampling on four stutions. The analysis of sediment fraction in estuary in dumai river had been dominated by mud substract. The result mean size wened very fine sand, of consistency organic material is ranging 7,37 - 24,01 mg/l. The result sorting value wered poorly kurtosis value were ektremly leptokurtic, and skewness dominant value were negative. Difference of fine grafain and type of sediment on estuary in Dumai River had effect by physics and chemical factor